Preferensi Dan Pola Konsumsi Mie Instan Pada Mahasiswa Jurusan Gizi Dan Analis Kesehatan Poltekkes Kemenkes Mataram Mataram Yang Tinggal Di Kost Dan Tidak Kost - Farizan Nuriz Risyanu; INyoman Adiyasa; Yuli Laraeni (Poltekkes Kemenkes Mataram, 2019)
Background: The shift in consumption patterns is possible because the noodles can be easily processed, presented with practical and can meet the tastes of most people, both adults and children. Promotion noodles with various types of products, sizes and at affordable prices in various places to make new noodle products quickly known by the public. Instant noodles are a favorite food of all people, especially for people who have a very busy life and reams much so that they do not have time to make or buy healthy food. This study aims to determine the preferences and consumption patterns in adolescents boarding instant noodles and not boarding the Department of Nutrition and Health Analyst at Ministry of Health Polytechnic Mataram. Methods: This study used observational methods cros sectional analytic approach. The number of samples in this study were as many as 56 among 28 adolescents and 28 adolescents not kos kos, sampling with simple random sampling. Collecting data through interviews using questionnaires and FFQ. The statistical test used to analyze the differences between variables using independent t-test. Research shows that teens boarding really like instant noodles 23 adolescents (82.1%) adolescents are not boarding like instant noodles were 24 adolescents (85.7%) and instant noodle consumption patterns of adolescent boarding and rooming boarding hightest usual teen consume fried noodles were 22 adolescents and 14 adolescents who consume regular boarding noodle soup. Conclusion: The results of the analysis of the data shows there are differences in consumption preferences of teenagers instant noodles boarding and rooming not (p = 0.000), no differences in the pattern of consumption of instant noodles teen boarding and boarding (p = 0.018). Keywords: Preferences, Teen, Consumption Patterns.